Distance Measurement of Low Reflectance Objects Using Indirect Time of Flight LiDAR - Agitta Rianaris; Nofriha Rahmayani Siregar; Hari Pratomo; Surip Kartolo; Syahrul Humaidi; Dwi Hanto (Journal of Technomaterial Physics, 2024)
Remote sensing is a system that enables data collection without physical contact with the object or its environment. Light detection and Ranging (LiDAR) technology is increasingly important in various industries, particularly developing autonomous vehicles. In autonomous vehicle applications, LiDAR is expected to detect multiple objects from high and low reflectance to make it easy to recognize its surrounding area. We have designed a biaxial LiDAR range finder system based on indirect time of flight technology, which has been tested to measure the distance of an object with high reflectance. In this work, we employ the system to measure the distance of an object with low reflectance from High Impact PolySterene (HIPS). The results show that the systems can measure objects from HIPS up to 33 m, which is lower than when the system measures an object with high reflectance.